Tax avoidance, endogenous social norms, and the comparison income effect - Alessandro Balestrino (Center for Economic Studies and ifo Institute (CESifo), 2006)
We present a model of income tax avoidance with heterogeneous agents, assuming the presence of a comparison income effect and of a psychic cost (disutility) of tax dodging. We analyse the policy preferences of the agents, and identify a median-voter political equilibrium. Paralleling previous results in the optimal taxation literature, we show that the comparison income effect calls for a high degree of progressivity of the income tax; additionally, we find that this tendence is strengthened by the psychic cost of avoidance. We then model the endogenous formation of the stigma attached to the act of avoidance as a conformism game. We argue that such stigma is motivated by the desire to make redistribution more effective, and that it is enhanced by the income comparison effect.
Keywords: D72; H26; H31; 330; Steuervermeidung; Steuersystem; Einkommensverteilung; Wirtschaftsmodell